Some aspects of on-line studying process in higher education institutions from Moldova - Valentina TÎRŞU (Eastern European Journal of Regional Studies, 2015)
Higher education institutions in Moldova go through a difficult transition period requested by implementing the principles of the Bologna Process, which lead to the restructuring of the national university education. The work includes a study of implementing e-learning in higher education institutions in Moldova. The results presented are obtained from the investigation conducted at Moldova State University on the quality of higher education. The platform MOODLE is growing. The importance of developing Moodle is significant and allows improving the quality of higher education. We believe that Moodle is an effective tool to facilitate the integration of young professionals in the labor market.